Jewish Politics in Eastern Europe - Jacobs, J. author. aut Link
XXV, 284 p.
Keywords: A collection of new, scholarly articles on the Jewish Workers' Bund - the first modern Jewish political party in Eastern Europe - written by prominent academics from eight countries. This work represents a broad range of perspectives, Jewish and non-Jewish, sympathetic to the Bund and critical of its work. The articles in this volume are fresh, make use of previously unused source material, and provide us with new perspectives on the significance of the Bund and its ideas.